Production of Butane from Methyl Ethyl Ketone over Pt/Al2O3 - Zahraa Al-Auda; Keith L. Hohn (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2023)
Methyl ethyl ketone (MEK) was catalytically converted to butane directly in one step over platinum (Pt) supported on alumina (Al2O3). The reaction was performed in the gas phase in a fixed bed reactor. Conversion of MEK to butane was achieved by hydrogenation of MEK to 2-butanol, dehydration of 2-butanol to butene, and further hydrogenation of butene to butane. The results showed that butane can be produced with selectivity reaching 95% depending on the operating conditions. The highest selectivity for butane was obtained at 220 °C and a H2/MEK molar ratio of 15. Copyright © 2023 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).